1987
DOI: 10.1161/01.str.18.6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cerebrovascular disease by combined extracranial and transcranial Doppler sonography. Experience in 1,039 patients.

Abstract: Results from 1,039 combined cervical and transcranial Doppler examinations are reported. Satisfactory transcranial signals were not found in 2.7% of the cases. Compared with angiography, the accuracy of transcranial criteria in assessing collateral flow over the circle of Willis was 94 and 88% for anterior and posterior circulation, respectively. The method also appeared very promising for detection of lesions of the intracranial arteries although the number of such cases with angiographic verification was lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
3
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(81 citation statements)
references
References 14 publications
(14 reference statements)
7
70
3
1
Order By: Relevance
“…1,9,[31][32][33] The statistical average group difference cannot be applied to an individual, in whom the exact configuration of the circle of Willis, 34 including the presence, caliber, and course of each artery, 35,36 and the degree of interhemispheric anatomic, [37][38][39] physiologic, and pathophysiologic differences are, a priori, unknown. 31,35,43,44 Large variability in side-to-side impedance indices and modest correlation coefficients for vessels that supposedly have no stenosis and hemispheres that are "seeing" the same circulating oxygen content and Hgb indicate that there is not such a tight agreement between sides in blood flow redistributions in response to a chronic oxygen deficit.…”
Section: Tolerance Intervals For Interhemispheric Differencesmentioning
confidence: 99%
“…1,9,[31][32][33] The statistical average group difference cannot be applied to an individual, in whom the exact configuration of the circle of Willis, 34 including the presence, caliber, and course of each artery, 35,36 and the degree of interhemispheric anatomic, [37][38][39] physiologic, and pathophysiologic differences are, a priori, unknown. 31,35,43,44 Large variability in side-to-side impedance indices and modest correlation coefficients for vessels that supposedly have no stenosis and hemispheres that are "seeing" the same circulating oxygen content and Hgb indicate that there is not such a tight agreement between sides in blood flow redistributions in response to a chronic oxygen deficit.…”
Section: Tolerance Intervals For Interhemispheric Differencesmentioning
confidence: 99%
“…9,38,44,45 Since the MCA segment alone was studied, the overall sensitivity decreased to 58.6% because isolated cerebral vasospasm of other segments was not detected. 38 This result prompted cerebral vasospasm diagnosis for other basal cerebral arteries.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%
“…12 The correlation between the inner angiographic diameter and the V m recorded by TCD has been clearly demonstrated for the MCA (0.54ϽrϽ0.901, PϽ0.001). 8,12,15,37,38,44 The correlation for the ICA with TCD (rϭϪ0.758, PϽ0.001) has only been reported by Harders and Gilbash. 12 In our series, an excellent correlation between diameter and velocity for the MCA was the same for each Doppler method.…”
mentioning
confidence: 95%
“…8 mL/min in the group of younger than 35 years old, and 260.0±33.0 mL/min in the group of older than 35. Dividing the subjects into age groups, Grolimund et al [1] found a significant decrease in MV in all arteries with increasing age. The mean difference between the oldest (> 70 years) and the youngest (< 30 years) age groups was 33%.…”
Section: Age and Sexmentioning
confidence: 99%
“…In 1987, Grolimund et al [1] reported flow velocities in a group of 535 patients with normal neurologic status and no localized increases in intracranial or extracranial Doppler velocities. The mean velocity of middle cerebral artery (MCA) was 57.3±14.8 cm/s; anterior cerebral artery (ACA), 49.2±15.1 cm/s; posterior cerebral artery (PCA), 37.2±10.4 cm/; internal carotid artery (ICA), 36.3±8.6 cm/s.…”
Section: Flow Velocitymentioning
confidence: 99%